Studying the Effectiveness of Ridostin® in the Experimental Form of Severe Acute Respiratory Syndrome - S. Ya. Loginova; V. N. Shchukina; S. V. Borisevich; R. A. Hamitov; V. A. Maksimov (Антибиотики и Химиотерапия, 2020)
Studies have been carried out on the effectiveness of the high molecular weight interferon inducer Ridostin® in relation to the experimental form of severe acute respiratory syndrome in Syrian hamsters. It is shown that Ridostin® is effective when used according to the prophylaxis regimen and post-exposure prophylaxis regimen. The coefficient of therapeutic effect was 47.5 and 55.0%, respectively. At the same time, there was a statistically high level of significant differences in the severity of the disease in animals treated with the medication according to the post-exposure prophylaxis regimen and control animals (P